Effects of RAGE Gene Polymorphisms on the Risk and Progression of Hepatocellular Carcinoma. Issue 34 (August 2015) - Su, Shih-Chi; Hsieh, Ming-Ju; Chou, Ying-Erh; Fan, Wen-Lang; Yeh, Chao-Bin; Yang, Shun-Fa; Giovanni, Tarantino.
<x xml:space="preserve">Abstract</x> Abstract Hepatocellular carcinoma (HCC) is a common malignancy of the liver, whose heterogeneous incidence reflects genetic variations among individuals in the main risk factors. The receptor for advanced glycosylation endproducts (RAGE) is a multiligand receptor and known to be implicated in various pathogenic conditions, such as diabetes, inflammatory disorder, Alzheimer disease, and cancer. In this study, the impact of RAGE gene polymorphisms on the susceptibility to hepatocarcinogenesis was explored. Four single-nucleotide polymorphisms (SNPs), rs184003 (1704G > T), rs1800624 (−374T > A), rs1800625 (−429T > C), and rs2070600 (Gly82Ser), as well as 1 gene polymorphism of RAGE gene, a 63 bp deletion allele (−407 to −345) were analyzed between 300 cancer-free subjects and 265 HCC cases. We detected a significant association of rs1800625 with the increased risk of HCC (odds ratio [OR], 2.565; 95% confidence interval [CI], 1.492–4.409 and adjusted odds ratio [AOR], 2.568; 95% CI, 1.418–4.653). However, patients who possess at least 1 polymorphic allele of rs1800625 are less prone to develop late-stage (stage III/IV, OR, 0.502; 95% CI, 0.243–1.037; P = 0.059 and AOR, 0.461; 95% CI, 0.219–0.970; P = 0.041) and large-size tumors (OR, 0.398; 95% CI, 0.183–0.864; P = 0.017 and AOR, 0.351; 95% CI, 0.157–0.781; P = 0.010). Furthermore, individuals bearing specific haplotypes of 4 RAGE SNPs tested are more inclined to have HCC. In conclusion, our data suggest a correlation of RAGE gene polymorphism rs1800625 with the early stage of liver tumorigenesis and implicate its protective role in the progression of HCC.